Spatial surveillance and risk factor assessment of ixodid ticks in cattle population of Himachal Shivalik hill zone of North-Western Himalayas. Issue 4 (19th May 2021) - Sharma, Kanika; Sharma, Devina; Moudgil, Aman Dev; Kumar, Pravesh; Thakur, Devesh
ABSTRACT: The present study aimed at assessing the epidemiology and associated risk factors of ixodid ticks from Shivalik hill zone of Himachal Pradesh, India. A total of 602 cattle of different age, breeds, and sex were screened for the occurrence of ixodid ticks from six districts from March, 2019 to February, 2020. The associated data were recorded for the risk factor assessment. The overall tick prevalence was recorded to be 66.4%. Three tick species were found prevalent viz ., Rhipicephalus ( Boophilus ) microplus (68.4%), Rhipicephalus ( Boophilus ) annulatus (30.85%), and Hyalomma anatolicum anatolicum (0.74%). The highest prevalence was recorded during the monsoon season (74.9%) (OR: 1.25; 0.65–1.86) followed by summer (65.3%) and lowest in winter season (59.4%) (OR: 0.64; 0.26–0.79). Agewise, tick infestation was observed to be highest in age group >1 year (76.5%) (OR: 6.37; 3.32–12.21) followed by age group >6 months–1 year (38.8%) (OR: 9.09; 4.67–17.69) and the lowest in ≤6 months age (29.3%). The prevalence rate was found to be more in female cattle (71.6%) in comparison to males (23.4%). Breedwise, the highest tick infestation was observed in cross-bred Jersey (69.8%) (OR: 3.51; 1.59–7.76) followed by cross-bred Holstein Friesian (69.6%) (OR: 0.95; 0.51–1.75) and lowest in indigenous cattle (45.0%). The risk factors related to management practices revealed that the prevalence of ixodid ticks was significantly ( P < 0.05) less when the animals were kept in pucca sheds with acaricide application done both on body and shed with reapplication in 3 months. The odds of tick infestation were high in cattle population in Solan (OR: 2.29; 1.05-5.02) and least in Hamirpur in comparison to Kangra region (reference district) when the regression analysis of the risk factors associated with tick prevalence was studied. The current study represents the first report determining the epidemiological status of ixodid ticks in Shivalik hill zone region and findings of the study would provide a basis for generating new and effective control strategies for management the management of ticks in cattle population of the region.